Level of physical activity of Indonesian esport athletes in the piala Presiden esport 2019 - Paramitha, Sandey Tantra; Hasan, Muhamad Fahmi; Ilsya, Marisa Noviyanti Fajrah; Anggraeni, Leni; Gilang Ramadhan, Muhammad (Jurnal SPORTIF : Jurnal Penelitian Pembelajaran, 2021)
Background: In the past years, Esport has been a phenomenon. It lies in a discussion of whether accepting esport as a part of sport categories or not. In fact, many argue about this because it has an impact on the physical activity and lifestyle of the players. This study focuses on the analysis of physical activity and lifestyle of esport athletes competing in annual sporting events throughout Indonesia. Method: In this study data collected from 50 athletes consisting of all men. The measurement method used in measuring the level of physical activity is the International Physical Activities Questionnaire (IPAQ). Result: From the completed questionnaire, it was found that the level of physical activity of the athletes reached 3120.2 (± 24.3) METs. This figure shows that athletes are still included in the category of high physical activity. Conclusion: The average level of physical activity of esport athletes is in the high category.